1967
DOI: 10.1039/tf9676302839
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of non-ionic surface-active agent + water systems

Abstract: Measurements of water vapour pressure and heat of mixing have been made at 25°C over a range of composition for the 'octyl-and decylhexaoxyethylene glycol monoether + water systems. The condensed binary phase diagrams show that only the system given by the higher homologue forms a lyotropic mesomorphic phase (middle phase) at 25°C. In both systems, the thermodynamic properties of the solutions are determined by the interaction of the hydrophilic groups with water. The water activity and heat of mixing are smoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1
1

Year Published

1978
1978
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 0 publications
1
44
1
1
Order By: Relevance
“…The phase behavior of their aqueous mixtures has also attracted considerable attention in view of both a fundamental interest in colloid science and the requirement for their practical use. It has been revealed that various mesomorphic phases are formed in aqueous mixtures of these surfactants depending on the chemical structure of the species, the composition of the mixture, and temperature (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). However, the interest so far has been rather restricted to the solution phase and liquid-crystalline phases, and much less attention has been addressed to the phase behavior in a solid state.…”
Section: Introductionmentioning
confidence: 98%
“…The phase behavior of their aqueous mixtures has also attracted considerable attention in view of both a fundamental interest in colloid science and the requirement for their practical use. It has been revealed that various mesomorphic phases are formed in aqueous mixtures of these surfactants depending on the chemical structure of the species, the composition of the mixture, and temperature (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). However, the interest so far has been rather restricted to the solution phase and liquid-crystalline phases, and much less attention has been addressed to the phase behavior in a solid state.…”
Section: Introductionmentioning
confidence: 98%
“…The phase science of the mixture systems of this type of surfactant and water has so far been a problem attracting considerable attention in fundamental colloid science and the practical application of the surfactants (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The highly viscous mesomorphic phases is unfavorable to transport the surfactant preparations in the industrial production process.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the measurements of V E m over the whole range of x we are unable to detect any discontinuity in the isotropic micellar phase to the hexagonal phase transition. If this transition is first order, as some authors (1) suggest, such a discontinuity in V m could be found by applying other volumetric techniques (18) such as those used in the study of order-disorder transition in thermotropic liquid crystals.…”
Section: Resultsmentioning
confidence: 97%
“…The phase diagram of {xCH 3 (CH 2 ) 9 O (CH 2 CH 2 O) 6 H + (1 − x)H 2 O} at the temperature 298.144 K has been reported in the literature by two independent groups. (1,2) This system exhibits lower critical solution temperature (l.c.s.t.) with a very flat minimum at T c = 332.15 K. The authors (1,2) found a substantial area (0.028 < x < 0.073) of the hexagonal phase in which lyotropic liquid crystals in equilibrium with the micellar phase are formed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation